Abdominal hysterectomy: comparative study between the simplified and Richardson’s techniques - Carpio Guzmán, Luis (2015)
Objectives: To determine differences between the simplified surgical technique and the Richardson’s technique for abdominal hysterectomy, in relation to surgical time, presentation and type of complications. Design: Descriptive, transversal, prospective and comparative study. Setting: Instituto Nacional Materno Perinatal, Lima, Peru. Participants: Patients undergoing abdominal hysterectomy. Interventions: Twenty six patients underwent abdominal hysterectomy with a simplified technique from February 1st, 2005, through May 31st, 2006 and compared with same number of patients intervened with the Richardson’s technique. Main outcome measures: Causes of hysterectomy, surgical time, presentation and type of complications. Results: The most frequent indication for abdominal hysterectomy was uterine myomas (76,9%). Complications were present in 17,3% of patients, with similar frequency with both techniques. The most frequent complications were local infection (7,6%) and urinary tract infection (5,8%). There were no significant differences in presentation and type of complications with both simplified and Richardson’s techniques. Surgical time (p<0,01) and hospitalization days (p<0,05) were less for patients operated with the simplified technique compared with Richardson’s technique. Conclusions: An alternative simplified technique to Richardson’s method could be used in abdominal hysterectomy with advantages in operative time and hospitalization days; 17,3% of patients presented some type of complication in the post operative period. We did not find association between the presence of complications and hysterectomy technique used, either simplified or Richardson´s.